2021
DOI: 10.3390/polym13132058
|View full text |Cite
|
Sign up to set email alerts
|

Vertical Orientation of Liquid Crystal on Polystyrene Substituted with n-Alkylbenzoate-p-oxymethyl Pendant Group as a Liquid Crystal Precursor

Abstract: We synthesized a series of polystyrene derivatives modified with precursors of liquid crystal (LC) molecules via polymer modification reactions. Thereafter, the orientation of the LC molecules on the polymer films, which possess part of the corresponding LC molecular structure, was investigated systematically. The precursors and the corresponding derivatives used in this study include ethyl-p-hydroxybenzoate (homopolymer P2BO and copolymer P2BO#, where # indicates the molar fraction of ethylbenzoate-p-oxymethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 78 publications
1
5
0
Order By: Relevance
“…It was found that the T g values of these polymers, PPHE#s, were higher than 100 °C due to their aromatic structure in the biphenyl-based PHE moiety. This result suggests that polystyrene substituted with phenylphenoxymethyl (PPHE#) containing the aromatic biphenyl moiety—a representative precursor in LC molecules—has a thermal stability which is higher than that of the previously reported PS derivatives containing alkyl aromatic LC precursors in the polymer—such as 4-( trans -4-ethylcyclohexyl)phenol [ 58 ], ethyl- p -hydroxybenzoate [ 59 ], and 4-ethyloxyphenol [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the T g values of these polymers, PPHE#s, were higher than 100 °C due to their aromatic structure in the biphenyl-based PHE moiety. This result suggests that polystyrene substituted with phenylphenoxymethyl (PPHE#) containing the aromatic biphenyl moiety—a representative precursor in LC molecules—has a thermal stability which is higher than that of the previously reported PS derivatives containing alkyl aromatic LC precursors in the polymer—such as 4-( trans -4-ethylcyclohexyl)phenol [ 58 ], ethyl- p -hydroxybenzoate [ 59 ], and 4-ethyloxyphenol [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the bulky groups of the biorenewable resources which are closely related to low surface energy value owing to the steric effect of bulky groups onto the polymer surface [ 51 , 52 , 53 , 54 , 55 , 56 , 57 ]. In addition, the LC cells made using the PS derivatives containing LC precursors in the polymer—such as 4-( trans -4-ethylcyclohexyl)phenol [ 58 ], ethyl- p -hydroxybenzoate [ 59 ], and 4-ethyloxyphenol [ 60 ]—showed the vertical alignment of LC molecules. It is suggested that the similarity of the chemical structure between the LC molecules and alignment layer can induce the vertical alignment of LC molecules.…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of the integrated peak areas of the oxymethyl peak and phenyl peaks revealed that the degree of substitution from chloromethyl to oxymethyl was ~100%. The high degree of substitution in this polymer modification reaction can be attributed to the electrophilicity of the benzylic carbon in poly(4-chloromethylstyrene) and to the structural stability of the phenolate anion as a nucleophile [ 53 ]. These polymers are soluble in many low boiling point solvents of medium polarities, such as THF and chloroform, and in polar aprotic solvents, such as N,N ′-dimethylformamide, N -methyl-2-pyrrolidone, and N,N ′-dimethylacetamide.…”
Section: Resultsmentioning
confidence: 99%
“…This is due to the long alkyl groups of the natural extracts, which are related to the low surface energy owing to the steric effect of the alkyl groups on the polymer film surface. In addition, the vertical alignment of the LC cells fabricated with PS derivatives having LC precursors in side chains, such as 4-( trans -4-ethylcyclohexyl)phenol [ 52 ], ethyl- p -hydroxybenzoate [ 53 ], and 4-ethyloxyphenol [ 54 ], was observed in spite of low substituent ratio from 20 mol%. In this case, it was found that the similarity between the chemical structure of the alignment layer and the LC molecule is a key factor in improving the LC alignment characteristics and inducing a stable alignment behavior.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to produce flexible plastic products because the post-baking and washing temperatures required for preparing the alignment layer from the PI derivative are too high [ 38 , 39 ]. Recently, a vertically aligned LC layer using a polystyrene (PS) derivative synthesized through a polymer substitution reaction has attracted much attention in the electro-optical field including flexible displays due to its advantages of excellent optical transparency and low-temperature processability [ 40 , 41 ]. PS derivatives, grafted with long alkyl groups, natural extracts, etc., have been studied to orient LC molecules vertically to the substrates using a non-contact method [ 42 , 43 ].…”
Section: Introductionmentioning
confidence: 99%